MENINGKATKAN MINAT BACA ANAK MELALUI PROGRAM PONDOK BACA ANAK HEBAT (AHE) DI DESA SINDANGKERTA KECAMATAN SINDANG KERTA KABUPATEN BANDUNG BARAT - Astarina Arif; Hevie Setia Gunawan (Jurnal Al Maesarah, 2023)
The low interest in reading in the community can result in a lack of knowledge obtained, lack of information obtained, lack of vocabulary and difficulties in managing information. One of the Darul Falah Real Work Lecture (KKN) programs is the provision of Great Children's Reading Cottage (AHE) in Sindangkerta village, Sindangkerta sub-district, West Bandung regency, which aims to increase public interest in reading. This KKN program collaborates with local community leaders such as the head of the RT, the head of the RW and also the whole community. The focus of the AHE reading cottage is for children aged 5-9 years. The method used in this activity is a qualitative method with a learning socialization approach and the provision of a children's reading hut commonly known as AHE. The provision of this AHE reading lodge has a positive impact on the local community, this can be seen from the results obtained in the form of an increase in reading for children aged 5-9 years. the existence of intensive tutoring individually.